THE pH TRENDS OF BEEF MEAT DURING TWO AGING PROCESSES - Maria-Cristina Gliga (Colciar); Adriana Paula David; Giorgiana Mihaela Catunescu; Ioana Maria Bodea; Manuel León Camacho; Maria Tofana (Agricultura)
The aim of this study was to assess the pH trend during the dry and wet aging processes, of two anatomical cuts (ribeye and sirloin), from two different beef breeds: Black Angus (BA) and Romanian Spotted (RS). Thus, acidity during the aging period was measured and the correlations between pH values and the qualitative attributes of meat were assessed and compared between two beef cattle breeds. The results showed that after 14 days of wet aging, the pH value decreased below 5.29 for all samples, with the lowest pH recorded for the Black Angus Ribeye (BAR) sample. In contrast, after 21 days of dry aging, the pH of the samples dropped below 5.33, with the lowest value (5.14) measured for the Black Angus Ribeye (BAR) sample. Thus, the BA breed exhibited a greater decrease in pH compared to RS, which could indicate an advanced proteolysis of proteins.